Angiosarcoma Arising in Ovarian Mucinous Tumor: A Challenge in Intraoperative Frozen Section Diagnosis - Surapan Khunamornpong; Jongkolnee Settakorn; Kornkanok Sukpan; Tip Pongsuvareeyakul; Sumalee Siriaunkgul (Case Reports in Pathology)
Angiosarcoma of the ovary is rare but represents an aggressive type of malignant ovarian neoplasms. The purpose of this report is to describe the features of angiosarcoma arising in mucinous tumor that was misinterpreted as a benign vascular proliferation during the intraoperative consultation. A 45-year-old woman presented with an abdominal mass for 1 month. Exploratory laparotomy was performed. A 35 cm right ovarian mass submitted for intraoperative consultation was a multicystic mucinous tumor with an 8 cm area of hemorrhagic lesion between cystic locules. The frozen section diagnosis was at least mucinous borderline tumor. The hemorrhagic area, which was intraoperatively interpreted as organizing vessels associated with previous hemorrhage, represented angiosarcoma in permanent sections. Angiosarcoma may present a challenge in intraoperative frozen section diagnosis of an ovarian mass. The presence of ectatic anastomosing vessels with dissecting growth appears to be the clue to a suspicion of angiosarcoma. The presence of endothelial atypia provides further support for the diagnosis. A macroscopic hemorrhagic area in an ovarian mucinous tumor should be evaluated with care, and the possibility of angiosarcoma should be borne in mind.